STUDY OF LEAD DIVALENT BIOSORPTION FROM AQUEOUS SOLUTIONS USING CORNCOB BIOMASS MODIFIED (zea mays) - Lavado Meza, Carmencita (2016)
Removing ions Pb (II) was investigated from aqueous solutions using biomass corn cob chemically modified with a 0,2 M NaOH solution, using a batch system, achieving 40% increase in adsorption capacity compared to similar unmodified (ZM). The corncob modified (MZM) was characterized by infrared spectroscopy Fourier transform (FTIR) determining presence of functional groups such as OH and carboxylic groups which would favor biosorption process, the surface area was determined to be the equal to 2,2 m2 /g. Likewise, adsorption capacity versus time MZM contact biosorbent dose, pH and initial concentration of Pb (II) solution were evaluated. The optimal conditions for the removal of Pb (II) were 4g/L MZM, stirring time 60 minutes and pH equal to 5,0. The kinetic data were fitted to the model of Pseudo Second Order, experimental equilibrium data were better adjusted to the Langmuir model, which would indicate a monolayer biosorption. The MZM has a maximum capacity of biosorption of 12,44 mg / g.